2022
DOI: 10.30821/jcims.v6i1.11189
|View full text |Cite
|
Sign up to set email alerts
|

RIMBA SINKRETIS: The Intersection of Islamic Spirituality in the Local Beliefs of the Indigenous Peoples of Makekal Hulu in Merangin District, Jambi Province

Abstract: <strong>Abstract</strong>:<strong> </strong><em>Rimba sinkretis </em>is a set of teachings and beliefs in the Jambi indigenous community, which shows a mixture of elements or understandings with other religions (Islam), which is revealed to be a belief. The ethnographic approach is known to be suitable for elemental and cultural studies. This study reveals three crucial topics: First<em>, </em>there isa meeting point of local religion with Islam which is believed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Ancestral gods and spirits that must be honored with rituals that have been regulated in their customary laws because they are believed to bring blessings of goodness and happiness. On the other hand, if this custom is not implemented, it can cause great sadness, disaster, and even dismay for their survival (Supian & Muspawi, 2022).…”
Section: An Interview With Temenggungmentioning
confidence: 99%
See 1 more Smart Citation
“…Ancestral gods and spirits that must be honored with rituals that have been regulated in their customary laws because they are believed to bring blessings of goodness and happiness. On the other hand, if this custom is not implemented, it can cause great sadness, disaster, and even dismay for their survival (Supian & Muspawi, 2022).…”
Section: An Interview With Temenggungmentioning
confidence: 99%
“…Some research on dialectics of religion, culture and local beliefs is very much found in various regions in Indonesia, especially between the Islamic religion (Ahad & Auliahadi, 2013;Al Qurtuby, 2020;Jubba, 2016;Pabajjah, 2020). Meanwhile, research on the religion of the Orang Rimba was also researched by (Mailinar & Nurdin, 2013) about the conception of the Suku Anak Dalam and Islam which is still mixed with the beliefs of their traditions such as besale and tahlinan, (Israhmat, 2016) about the Suku Anak Dalam belief system, and the intersection of Islamic spirituality with indigenous peoples (Supian & Muspawi, 2022). However, no one has seen the dialectic between the Suku Anak Dalam and Islam beliefs about mantras, especially the Jambi Orang Rimba community.…”
Section: Introductionmentioning
confidence: 99%